(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency, cause, management and outcome of ruptured uterus in both units of Bolan Medical Complex Hospital in Baluchistan, Pakistan. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Department of Gynecology and Obstetrics, Bolan Medical Complex Hospital, Quetta from 1st January to 31st December 2016. Materials and Methods: It was done to describe the frequency, cause, treatment, complications and maternal and fetal morbidity and mortality associated with ruptured uterus. A structured questionnaire was used to collect information about each case from different persons and registers. Results: During the study of one year a total of 68 cases of ruptured uterus and 12000 hospital deliveries were recorded for a ratio of 1:177. Causes of rupture were multiparity 29.4%, obstructed labour 14.7%, oxytocin induced 7.4% and uterine scar 47.7%. Most patients were multipara and rupture was complete in 88.2% of patients. Site of the rupture was in lower uterine segment in 50% and in right lateral segment in 17.7%. 14.7% of patients had associated urinary bladder injury. Total abdominal hysterectomy was performed in 17.6% of patients and repair was done in 82.4%. Vesico-vaginal fistula and wound infection were the rare postoperative complications. Maternal mortality rate was 11.8% and fetal mortality rate was 85.3%. Conclusion: This study reveals that an integrated effort to prevent the causes of uterine rupture and ensure effective management to reduce maternal and perinatal morbidity and mortality is needed.